Mapping Political Rhetoric: A Scientometric Analysis of Figurative Language in Political Discourse (2014-2024) - Nugraha, Danang Satria; Budiono, Taat (Universitas PGRI Sumatera Barat, 2025)
Political speech plays a crucial role in shaping public perception, influencing emotions, and constructing ideological narratives. This study employs a scientometric approach to analyze research trends on figurative language in political discourse over the past decade (2014–2024). Using bibliometric data from the Scopus database, we examined 870 journal articles to identify key themes, publication trends, and dominant research clusters. Findings indicate significant growth in the field, particularly from 2018 onward, reflecting increased scholarly interest in political rhetoric. Social Media and Society, Cogent Arts & Humanities, and Theory and Practice in Language Studies emerged as leading publication venues. Thematic analysis revealed four major research clusters: (1) Language and Rhetoric, focusing on metaphor, framing, and discourse strategies; (2) Politician Identity, covering leadership, charisma, and political messaging; (3) Political Discourse, highlighting ideology, persuasion, and propaganda; and (4) Political Events, examining how figurative language is used during elections, crises, and debates. While this study provides a macro-level overview of research on figurative language in politics, it also highlights gaps in qualitative analysis. Future research should integrate rhetorical criticism with scientometric approaches to provide deeper insights into how figurative language influences political engagement. Additionally, expanding the dataset to include diverse linguistic and cultural perspectives would enhance the understanding of global rhetorical strategies. By mapping this field, the study contributes to a more comprehensive knowledge of how language and power interact in political communication.